AMB silicon nitride ceramic copper clad sheet and preparation method thereof

By printing active solder paste on a ceramic substrate and applying a nano-metal organic solution to the copper-clad laminate, the problems of insufficient bonding strength and high porosity of AMB ceramic copper-clad laminate in industrial production are solved, achieving a balance of high bonding strength, low void ratio and excellent etching effect, which is suitable for large-scale industrial production.

CN116133269BActive Publication Date: 2026-11-06ZHUZHOU TORCH SPARK PLUG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310068265.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-17
Publication Date
2026-11-06
Estimated Expiration
2043-01-17

AI Technical Summary

Technical Problem

Existing AMB ceramic copper-clad laminate technology suffers from problems such as insufficient bonding strength, high porosity, and complex etching processes in large-scale industrial production, making it difficult to simultaneously achieve a balance between high bonding strength, low porosity, and excellent etching effect.

Method used

By printing active solder paste on a ceramic substrate and applying a nano-metal organic solution to a copper-clad sheet, a TiN reaction layer is formed through the combination of alloy powder and nano-metal particles, which improves the bonding strength. Furthermore, by controlling the coating thickness and the composition of the active solder paste, the soldering process is optimized and bubble defects are reduced.

Benefits of technology

The prepared AMB silicon nitride ceramic copper-clad sheet has high bonding strength, low void ratio, and uniform and clear lines after etching, meeting the needs of large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116133269B_ABST
    Figure CN116133269B_ABST
Patent Text Reader

Abstract

This application discloses an AMB silicon nitride ceramic copper-clad laminate, comprising a ceramic substrate, a copper-clad laminate, an active solder paste, and a nano-metal organic solution. The active solder paste is printed on both sides of the ceramic substrate, and the nano-metal organic solution is applied to one side of the copper-clad laminate. The copper-clad laminate coated with the nano-metal organic solution is then bonded to both sides of the ceramic substrate printed with the active solder paste to obtain the AMB silicon nitride ceramic copper-clad laminate. The product prepared by this application exhibits high bonding strength between the copper-clad laminate and the ceramic substrate, fewer bubble defects after brazing, and uniform and clear lines in subsequent etching processes, meeting the current requirements for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to an AMB silicon nitride ceramic copper-clad sheet and its preparation method, belonging to the field of ceramic-metal composite material preparation technology. Background Technology

[0002] There are two main production processes for ceramic surface metallization: Direct Copper Ceramic (DCB) and Active Metal Bonding (AMB). DCB involves directly bonding copper to the ceramic using an oxygen-containing eutectic solution. AMB utilizes a small amount of active elements in the solder to chemically react with the ceramic at high temperatures, generating a reaction layer that can be wetted by the liquid solder, thus achieving high bonding strength between the ceramic and metal. AMB is a further development of DBC technology, and AMB offers superior overall performance.

[0003] With the development of power conversion fields such as electric vehicles, solar and wind power plants, various industries have increasingly higher requirements for ceramic copper-clad laminates (CCLs) used in packaging modules, demanding high power, high heat dissipation, and high reliability. However, conventional AMB CCLs are typically soldered using silver-copper-titanium solder paste. Products manufactured using this method often suffer from numerous solder holes and complex subsequent etching processes, resulting in a complex overall process with high post-processing requirements and a low product yield. Other advanced AMB CCL manufacturing processes require more sophisticated equipment. These methods are more suitable for laboratory research and are prone to various problems in large-scale industrial production, failing to meet the demands of current mass production.

[0004] Japanese Insulator Co., Ltd.'s invention patent WO2021015122A1 discloses a bonding substrate and a method for manufacturing the bonding substrate. The soldering material is a material containing silver (Ag) and an active metal powder. The active metal is at least one metal selected from titanium (Ti) and zirconium (Zr). The final material has good bonding strength, but the cost of using materials such as silver is too high. The product prepared by traditional silver-titanium-copper active solder paste also has a high porosity.

[0005] Chinese patent CN 113795091A - A method for preparing ceramic circuit boards by low-temperature sintering discloses an active metal solder paste composed of nano-metal particles of gold, silver, and copper and active metal particles of titanium, cerium, and gallium. Its main feature is to reduce the sintering temperature, but its cost is still relatively high, and the bonding strength and porosity of the product are difficult to guarantee.

[0006] Chinese Patent CN 112319078B - A method for preparing a ceramic circuit board discloses an active metal brazing paste. The active metal brazing paste is composed of a metal component and an active metal component. The metal component is selected from silver, copper, nickel, tin, zinc and indium, and the active metal component is selected from titanium, zirconium, hafnium, chromium and nickel. It mainly solves the problem of rapid etching of circuits. The final peel strength of the product is up to 16 N / mm, but the bonding strength is relatively low.

[0007] Existing technologies typically focus on improving only one property of ceramic copper-clad laminates, because improving even one property is difficult, let alone achieving a balance between good bonding strength, low void ratio, and excellent post-etching process. Summary of the Invention

[0008] To address the aforementioned issues, an AMB silicon nitride ceramic copper-clad laminate and its preparation method are provided. This product exhibits high bonding strength between the copper-clad laminate and the ceramic substrate, fewer bubble defects after brazing, and uniform and clear lines in subsequent etching processes, meeting the current requirements for large-scale industrial production.

[0009] According to one aspect of this application, an AMB silicon nitride ceramic copper-clad sheet is provided, comprising a ceramic substrate, a copper-clad sheet, an active solder paste, and a nano-metal organic solution;

[0010] The active solder paste is printed on both sides of the ceramic substrate, and the nano-metal organic solution is applied to one side of the copper-clad sheet. The copper-clad sheet with the nano-metal organic solution is then bonded to both sides of the ceramic substrate printed with the active solder paste to obtain the AMB silicon nitride ceramic copper-clad sheet.

[0011] Optionally, the active solder paste comprises, by weight, 82-86% alloy powder, 0.6-2.5% binder, 12-15% solvent and 0.2-0.6% thixotropic agent;

[0012] The alloy powder is one of copper-titanium alloy, copper-titanium-boron alloy, or copper-tin-titanium alloy.

[0013] Optionally, in copper-titanium alloys, the titanium content is 5-35% by mass percentage, and the remainder is copper;

[0014] In copper-titanium-boron alloys, the titanium content is 5-35%, the boron content is 5-10%, and the remainder is copper;

[0015] In copper-tin-titanium alloys, titanium content is 5-15%, tin content is 5-25%, and the remainder is copper.

[0016] Optionally, the binder is ethyl cellulose, the solvent is one of dodecyl alcohol ester, butyl carbitol acetate, oleic acid or terpineol, and the thixotropic agent is hydrogenated castor oil.

[0017] Optionally, the nano-metal organic solution comprises 20-70% nano-metal particles and the remainder is an organic solvent, by mass percentage.

[0018] Optionally, the nano-metal particles are one or more of titanium, zirconium, tin, gallium, indium, and bismuth; the organic solvent is one of terpineol, turpentine, diethylene glycol ethyl ether, diethylene glycol, dodecyl alcohol ester, diethylene glycol ethyl ether acetate, and diethylene glycol butyl ether acetate.

[0019] The particle size of the nano-metal particles is 30-80 nm.

[0020] Preferably, the particle size of the nano-metal particles is 30-50 nm.

[0021] Optionally, the nano-metal particles are titanium, gallium, tin and indium, with an addition weight ratio of 3:2:2:1; the particle size of titanium is 10 nm larger than that of the other metal particles.

[0022] Optionally, the thickness of the printed active solder paste coating is 10-15 μm, the ceramic substrate is a silicon nitride ceramic substrate, and the copper clad sheet is an oxygen-free copper sheet.

[0023] According to another aspect of this application, a method for preparing the above-mentioned AMB silicon nitride ceramic copper-clad sheet is also disclosed, comprising the following steps:

[0024] (1) Clean the ceramic substrate and copper-clad sheet with organic solvent, print active solder paste on both sides of the ceramic substrate, and apply nano-metal organic solution to one side of the copper-clad sheet.

[0025] (2) The copper-clad sheet coated with nano-metal organic solution is attached to the two sides of the ceramic substrate printed with active solder paste, fixed with a clamp, placed in a vacuum brazing furnace for welding, and finally cooled naturally with the furnace to obtain the AMB silicon nitride ceramic copper-clad sheet.

[0026] Optionally, the organic solvent in step (1) is ethanol or acetone; the welding process in step (2) involves controlling the vacuum level at 5 × 10⁻⁶. -3 Below Pa, heat to 440-460℃ and hold for 0.5-2 hours, then heat to 880-920℃ and hold for 0.5-2 hours.

[0027] The beneficial effects of this application include, but are not limited to:

[0028] 1. According to the AMB silicon nitride ceramic copper-clad sheet of this application, the inventors have found that when a single solder paste or slurry is applied to a ceramic substrate, problems such as significant loss of active technical elements, easy oxidation of elements, or the influence of micro-seams on the surface of the copper sheet on wetting are likely to occur during the welding process, ultimately affecting the void ratio and bonding strength. However, copper sheets are not suitable for direct application of solder paste, as it can easily affect subsequent etching.

[0029] Therefore, this application limits the printing of active solder paste on a ceramic substrate and the application of a nano-metal organic solution on the copper-clad laminate. On the one hand, this allows the alloy components in the solder paste and the metal particles in the nano-metal organic solution to complement each other, avoiding situations where solder paste is missed or the metal particles are not fully covered, thus increasing the void ratio. On the other hand, it also allows the titanium elements in the solder paste to quickly dissolve into the silicon nitride ceramic and react with silicon nitride to form TiN, improving the bonding strength between the copper foil and the ceramic. The nano-metal organic solution can also quickly compensate for the burn-off of active metal elements during the soldering process, reducing the void ratio.

[0030] 2. According to the AMB silicon nitride ceramic copper-clad sheet of this application, by limiting the coating thickness of the printed active solder paste, it is possible to avoid the coating being too small, which would reduce the bonding strength and resistance to thermal shock, and also to avoid the coating being too large, which would affect the subsequent etching process and result in unclear circuits after etching.

[0031] 3. The AMB silicon nitride ceramic copper-clad sheet according to this application, by limiting the active solder paste to be composed of copper-titanium or copper-titanium-boron or copper-tin-titanium alloy and other components, can reduce the oxidation deactivation of titanium and improve wettability. At the same time, boron has very low solid solubility in copper and is easy to agglomerate at the interface to reduce surface energy and improve bonding strength. Tin in copper-tin-titanium alloy can reduce the surface tension of the alloy during brazing and improve the wettability to the ceramic substrate, thereby improving the bonding strength between the ceramic substrate and the copper sheet.

[0032] 4. The AMB silicon nitride ceramic copper-clad sheet of this application, by using and defining the type, addition ratio and particle size of nano-metal particles in the nano-metal organic solution, with titanium particles having a slightly larger size to compensate for the portion lost due to oxidation and burning, can also promote the reaction with silicon nitride, further improve wettability, and help improve bonding strength. In addition, with the addition of gallium, tin and indium, the spreading performance of solder paste during welding can be improved, the formation of intermetallic compounds can be reduced, and the adhesion strength between the copper sheet and the ceramic substrate can be guaranteed.

[0033] 5. The method for preparing AMB silicon nitride ceramic copper-clad sheets according to this application is simple to operate, requires low equipment, and produces copper-clad sheets with high bonding strength to ceramic substrates. It also produces fewer bubble defects after brazing and results in uniform and clear lines in subsequent etching processes, meeting the current needs of large-scale industrial production. Attached Figure Description

[0034] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:

[0035] Figure 1 This is an image showing the etching effect of the AMB silicon nitride ceramic copper-clad sheet in Example 3 of this application;

[0036] Figure 2 This is an image showing the etching effect of a 2AMB silicon nitride ceramic copper-clad sheet, which is a comparative example of this application.

[0037] Figure 3 This is an ultrasonic scanning microscope image of the AMB silicon nitride ceramic copper-clad sheet from Example 1 of this application;

[0038] Figure 4 This is an ultrasonic scanning microscope image of the copper-clad silicon nitride ceramic sheet of Example 3AMB of this application;

[0039] Figure 5 This is an ultrasonic scanning microscope image of the AMB silicon nitride ceramic copper-clad sheet from Embodiment 5 of this application.

[0040] Figure 6 This is an ultrasonic scanning microscope image of the 2AMB silicon nitride ceramic copper-clad sheet, which is a comparative example of this application. Detailed Implementation

[0041] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. The reagents and raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods in the art or as per the product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described in this patent are for illustrative purposes only.

[0043] The printing process for printing active solder paste onto silicon nitride ceramic substrates described in the embodiments and comparative examples of this application is a conventional screen printing process in the prior art. Vacuum brazing furnace model: Zhengzhou Kejia Electric Furnace Co., Ltd. KJ-M1200-12G.

[0044] Example 1

[0045] AMB silicon nitride ceramic copper-clad laminate is prepared from a ceramic substrate, copper-clad laminate, active solder paste, and nano-metal organic solution. The active solder paste, by weight, comprises 82% alloy powder, 2.5% binder, 15% solvent, and 0.5% thixotropic agent. The alloy powder is a copper-titanium alloy with 10% titanium and the remainder being copper. The binder is ethyl cellulose, the solvent is dodecyl alcohol ester, and the thixotropic agent is hydrogenated castor oil. The nano-metal organic solution, by weight percentage, comprises 50% nano-metal particles, with the remainder being organic solvent; the organic solvent is terpineol.

[0046] The nano-metal particles are titanium, gallium, tin, and indium, added in a weight ratio of 3:2:2:1; the particle size of gallium, tin, and indium is 40 nm, while the particle size of titanium is 10 nm larger than that of the other metal particles. The thickness of the printed active solder paste coating is 12 μm. The ceramic substrate is a silicon nitride ceramic substrate, and the copper cladding is an oxygen-free copper sheet.

[0047] The preparation method includes the following steps:

[0048] (1) Clean the ceramic substrate and copper-clad sheet with organic solvent, print active solder paste on both sides of the ceramic substrate, and apply nano-metal organic solution to one side of the copper-clad sheet.

[0049] (2) The copper-clad sheet coated with nano-metal organic solution is attached to the two sides of the ceramic substrate printed with active solder paste, fixed with a clamp, placed in a vacuum brazing furnace for welding, and finally cooled naturally with the furnace to obtain the AMB silicon nitride ceramic copper-clad sheet.

[0050] In step (1), the organic solvent is ethanol; in step (2), the welding process involves controlling the vacuum level at 5 × 10⁻⁶. -3 Below Pa, heat to 450℃, hold for 1 hour, then heat to 900℃ and hold for 1 hour.

[0051] Example 2

[0052] AMB silicon nitride ceramic copper-clad laminate is prepared from a ceramic substrate, a copper-clad laminate, an active solder paste, and a nano-metal organic solution. The active solder paste, by weight, comprises 86% alloy powder, 0.8% binder, 13% solvent, and 0.2% thixotropic agent. The alloy powder is a copper-titanium-boron alloy with 10% titanium, 5% boron, and the remainder copper. The binder is ethyl cellulose, the solvent is butyl carbitol acetate, and the thixotropic agent is hydrogenated castor oil. The nano-metal organic solution, by weight percentage, comprises 20% nano-metal particles, with the remainder being an organic solvent, specifically diethylene glycol ethyl ether.

[0053] The nano-metal particles are titanium, gallium, tin, and indium, added in a weight ratio of 3:2:2:1; the particle size of gallium, tin, and indium is 30 nm, while the particle size of titanium is 10 nm larger than that of the other metal particles. The thickness of the printed active solder paste coating is 12 μm. The ceramic substrate is a silicon nitride ceramic substrate, and the copper cladding is an oxygen-free copper sheet.

[0054] The preparation method includes the following steps:

[0055] (1) Clean the ceramic substrate and copper-clad sheet with organic solvent, print active solder paste on both sides of the ceramic substrate, and apply nano-metal organic solution to one side of the copper-clad sheet.

[0056] (2) The copper-clad sheet coated with nano-metal organic solution is attached to the two sides of the ceramic substrate printed with active solder paste, fixed with a clamp, placed in a vacuum brazing furnace for welding, and finally cooled naturally with the furnace to obtain the AMB silicon nitride ceramic copper-clad sheet.

[0057] In step (1), the organic solvent is acetone; in step (2), the welding process involves controlling the vacuum level at 5 × 10⁻⁶. -3 Below Pa, heat to 440℃, hold for 0.5h, then heat to 880℃ and hold for 2h.

[0058] Example 3

[0059] AMB silicon nitride ceramic copper-clad laminate is prepared from a ceramic substrate, a copper-clad laminate, an active solder paste, and a nano-metal organic solution. The active solder paste, by weight, comprises 84% ​​alloy powder, 2% binder, 13.5% solvent, and 0.5% thixotropic agent. The alloy powder is a copper-titanium-boron alloy with 35% titanium, 10% boron, and the remainder copper. The binder is ethyl cellulose, the solvent is oleic acid, and the thixotropic agent is hydrogenated castor oil. The nano-metal organic solution, by weight percentage, comprises 70% nano-metal particles, with the remainder being an organic solvent, specifically diethylene glycol ethyl ether acetate.

[0060] The nano-metal particles are titanium, gallium, tin, and indium, added in a weight ratio of 3:2:2:1; the particle size of gallium, tin, and indium is 60 nm, while the particle size of titanium is 10 nm larger than that of the other metal particles. The thickness of the printed active solder paste coating is 15 μm. The ceramic substrate is a silicon nitride ceramic substrate, and the copper cladding is an oxygen-free copper sheet.

[0061] The preparation method includes the following steps:

[0062] (1) Clean the ceramic substrate and copper-clad sheet with organic solvent, print active solder paste on both sides of the ceramic substrate, and apply nano-metal organic solution to one side of the copper-clad sheet.

[0063] (2) The copper-clad sheet coated with nano-metal organic solution is attached to the two sides of the ceramic substrate printed with active solder paste, fixed with a clamp, placed in a vacuum brazing furnace for welding, and finally cooled naturally with the furnace to obtain the AMB silicon nitride ceramic copper-clad sheet.

[0064] In step (1), the organic solvent is ethanol; in step (2), the welding process involves controlling the vacuum level at 5 × 10⁻⁶. -3 Below Pa, heat to 460℃, hold for 2 hours, then heat to 920℃ and hold for 0.5 hours.

[0065] Example 4

[0066] AMB silicon nitride ceramic copper-clad laminate is prepared from a ceramic substrate, a copper-clad laminate, an active solder paste, and a nano-metal organic solution. The active solder paste, by weight, comprises 84% ​​alloy powder, 2.5% binder, 13% solvent, and 0.5% thixotropic agent. The alloy powder is a copper-tin-titanium alloy with 5% titanium, 25% tin, and the remainder copper. The binder is ethyl cellulose, the solvent is one of terpineol, and the thixotropic agent is hydrogenated castor oil. The nano-metal organic solution, by weight percentage, comprises 50% nano-metal particles, with the remainder being an organic solvent; the organic solvent is diethylene glycol butyl ether acetate.

[0067] The nano-metal particles are titanium, gallium, tin, and indium, added in a weight ratio of 3:2:2:1; the particle size of gallium, tin, and indium is 40 nm, while the particle size of titanium is 10 nm larger than that of the other metal particles. The thickness of the printed active solder paste coating is 12 μm. The ceramic substrate is a silicon nitride ceramic substrate, and the copper cladding is an oxygen-free copper sheet.

[0068] The preparation method includes the following steps:

[0069] (1) Clean the ceramic substrate and copper-clad sheet with organic solvent, print active solder paste on both sides of the ceramic substrate, and apply nano-metal organic solution to one side of the copper-clad sheet.

[0070] (2) The copper-clad sheet coated with nano-metal organic solution is attached to the two sides of the ceramic substrate printed with active solder paste, fixed with a clamp, placed in a vacuum brazing furnace for welding, and finally cooled naturally with the furnace to obtain the AMB silicon nitride ceramic copper-clad sheet.

[0071] In step (1), the organic solvent is acetone; in step (2), the welding process involves controlling the vacuum level at 5 × 10⁻⁶. -3 Below Pa, heat to 450℃, hold for 1 hour, then heat to 900℃ and hold for 1 hour.

[0072] Example 5

[0073] AMB silicon nitride ceramic copper-clad laminate is prepared from a ceramic substrate, a copper-clad laminate, an active solder paste, and a nano-metal organic solution. The active solder paste, by weight, comprises 85% alloy powder, 1% binder, 13.4% solvent, and 0.6% thixotropic agent. The alloy powder is a copper-tin-titanium alloy with 15% titanium, 5% tin, and the remainder copper. The binder is ethyl cellulose, the solvent is butyl carbitol acetate, and the thixotropic agent is hydrogenated castor oil. The nano-metal organic solution, by weight percentage, comprises 50% nano-metal particles, with the remainder being an organic solvent, specifically diethylene glycol ethyl ether.

[0074] The nano-metal particles are titanium, gallium, tin, and indium, added in a weight ratio of 3:2:2:1; the particle size of gallium, tin, and indium is 40 nm, while the particle size of titanium is 10 nm larger than that of the other metal particles. The thickness of the printed active solder paste coating is 13 μm. The ceramic substrate is a silicon nitride ceramic substrate, and the copper cladding is an oxygen-free copper sheet.

[0075] The preparation method includes the following steps:

[0076] (1) Clean the ceramic substrate and copper-clad sheet with organic solvent, print active solder paste on both sides of the ceramic substrate, and apply nano-metal organic solution to one side of the copper-clad sheet.

[0077] (2) The copper-clad sheet coated with nano-metal organic solution is attached to the two sides of the ceramic substrate printed with active solder paste, fixed with a clamp, placed in a vacuum brazing furnace for welding, and finally cooled naturally with the furnace to obtain the AMB silicon nitride ceramic copper-clad sheet.

[0078] In step (1), the organic solvent is acetone; in step (2), the welding process involves controlling the vacuum level at 5 × 10⁻⁶. -3 Below Pa, heat to 460℃, hold for 1 hour, then heat to 920℃ and hold for 1 hour.

[0079] Comparative Example 1

[0080] The difference between Comparative Example 1 and Example 3 is that Comparative Example 1 does not use nano-metal organic solution to coat the copper-clad sheet, but only active solder paste.

[0081] Comparative Example 2

[0082] The difference between Comparative Example 2 and Example 3 is that the active solder paste used in Comparative Example 2 is a silver-copper-titanium solder paste, which is 70% silver, 28% copper and 2% titanium by mass percentage.

[0083] Comparative Example 3

[0084] The difference between Comparative Example 3 and Example 3 is that the nano-metal-organic particles in Comparative Example 3 are titanium, tin and indium, and the weight ratio of addition is 3:2:1.

[0085] Comparative Example 4

[0086] The difference between Comparative Example 4 and Example 3 is that the titanium and other metal particles in the nano-metal-organic particles of Comparative Example 4 have the same particle size, which is 60 nm.

[0087] Experimental Example

[0088] 1. The peel strength and void ratio of the AMB silicon nitride ceramic copper-clad sheets prepared in Examples 1-5 and Comparative Examples 1-4 were tested respectively. The test results are shown in Table 1.

[0089] (1) Peel strength test method: Refer to the peel strength test criteria for metal-coated sheets in the IPC-TM-650 test method manual. Multiple 3mm wide copper foils were etched on the surface of four sets of samples. The copper foil layer was vertically peeled off at a speed of 50mm / min on a universal testing machine. The average value of the three copper foil measurements on the same sample was taken as the result.

[0090] (2) Void rate test method: The void rate of the sample was scanned and detected by ultrasonic scanning microscope (model SAM301). The scanning range was 320*320mm, the test probe was 50MHz, and f=10mm.

[0091] Figures 3-6 The images shown are ultrasonic scanning microscope images of Examples 1, 3, 5 and Comparative Example 2.

[0092] Table 1. Results of peel strength and void ratio tests

[0093]

[0094]

[0095] The above data shows that the AMB silicon nitride ceramic copper-clad sheets prepared using the parameters defined in this application exhibit high bonding strength, strong peel resistance, and a void ratio that can be controlled below 0.5%, demonstrating excellent performance. Figures 3-5 It is known that the AMB silicon nitride ceramic copper-clad sheet prepared in this application has an extremely low void ratio, and the voids are not obvious after coloring.

[0096] Comparative Example 1 used a single-active solder paste, and the final results showed that its bond strength was average and the void ratio was slightly high. The reason for this was that there was a large loss of active elements during the soldering process, resulting in poor wettability. Comparative Example 2 used a traditional silver-copper-titanium solder paste, and the final results showed that its bond strength was poor and the void ratio was high. Figure 6 It is evident that: Comparative Example 3, which did not use gallium, showed that its bonding strength was average and its void ratio was slightly high. The reason for this was that the reaction produced a large amount of Cu6Sn5 intermetallic compound, resulting in poor solder paste spreading performance. Comparative Example 4, which used titanium particles with the same particle size as other elements, also showed that its bonding strength was average and its void ratio was slightly high. The reason for this was that titanium was oxidized and burned off during the welding process, resulting in poor wettability.

[0097] 2. Comparison of subsequent etching effects

[0098] The AMB silicon nitride ceramic copper-clad wafers of Example 3 and Comparative Example 2 were etched using the same conventional wet etching process. The etching effect of the AMB silicon nitride ceramic copper-clad wafer of Example 3 is as follows: Figure 1 As shown, the etching effect of the AMB silicon nitride ceramic copper-clad sheet in Comparative Example 2 is as follows: Figure 2 As shown.

[0099] As shown in the figure, the AMB silicon nitride ceramic copper-clad sheet prepared by the method of this application is free of bubbles and has uniform and clear lines; the AMB silicon nitride ceramic copper-clad sheet of Comparative Example 2 has bubbles and the edges of the lines are blurred and uneven.

[0100] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. An AMB silicon nitride ceramic copper-clad sheet, characterized in that, Including ceramic substrates, copper-clad laminates, active solder paste, and nano-metal organic solutions; The active solder paste is printed on both sides of the ceramic substrate, and the nano-metal organic solution is applied to one side of the copper-clad sheet. The copper-clad sheet with the nano-metal organic solution is bonded to the two sides of the ceramic substrate printed with the active solder paste and soldered to obtain the AMB silicon nitride ceramic copper-clad sheet. The active solder paste comprises, by weight percentage, 82-86% alloy powder, 0.6-2.5% binder, 12-15% solvent, and 0.2-0.6% thixotropic agent; the alloy powder is one of copper-titanium alloy, copper-titanium-boron alloy, or copper-tin-titanium alloy. The nano-metal organic solution comprises 20-70% nano-metal particles, with the remainder being organic solvents; The nano-metal particles are titanium, gallium, tin and indium, with an addition weight ratio of 3:2:2:1; the particle size of titanium is 10 nm larger than that of the other metal particles.

2. The AMB silicon nitride ceramic copper-clad sheet according to claim 1, characterized in that, By mass percentage, the titanium content in copper-titanium alloys is 5-35%, with the remainder being copper; In copper-titanium-boron alloys, the titanium content is 5-35%, the boron content is 5-10%, and the remainder is copper; In copper-tin-titanium alloys, titanium content is 5-15%, tin content is 5-25%, and the remainder is copper.

3. The AMB silicon nitride ceramic copper-clad sheet according to claim 1, characterized in that, The binder is ethyl cellulose, the solvent is one of dodecyl alcohol ester, butyl carbitol acetate, oleic acid or terpineol, and the thixotropic agent is hydrogenated castor oil.

4. The AMB silicon nitride ceramic copper-clad sheet according to claim 3, characterized in that, The organic solvent is one of terpineol, turpentine oil, diethylene glycol ethyl ether, diethylene glycol, dodecyl alcohol ester, diethylene glycol ethyl ether acetate, and diethylene glycol butyl ether acetate; The particle size of the nano-metal particles is 30-80 nm.

5. The AMB silicon nitride ceramic copper-clad sheet according to claim 1, characterized in that, The thickness of the printed active solder paste coating is 10-15μm. The ceramic substrate is a silicon nitride ceramic substrate, and the copper cladding is an oxygen-free copper sheet.

6. A method for preparing an AMB silicon nitride ceramic copper-clad sheet as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Clean the ceramic substrate and copper-clad sheet with organic solvent, print active solder paste on both sides of the ceramic substrate, and apply nano-metal organic solution to one side of the copper-clad sheet; (2) The copper-clad sheet coated with nano-metal organic solution is attached to the two sides of the ceramic substrate printed with active solder paste, fixed with a clamp, placed in a vacuum brazing furnace for welding, and finally cooled naturally with the furnace to obtain the AMB silicon nitride ceramic copper-clad sheet.

7. The preparation method according to claim 6, characterized in that, The organic solvent in step (1) is ethanol or acetone; The welding process in step (2) involves controlling the vacuum level at 5×10. -3 Below Pa, heat to 440-460℃ and hold for 0.5-2 hours, then heat to 880-920℃ and hold for 0.5-2 hours.

Citation Information

Patent Citations

  • A method for preparing a ceramic circuit board

    CN112319078B

  • Method for preparing ceramic circuit board through low-temperature sintering

    CN113795091A

  • Bonded substrate, and method for manufacturing bonded substrate

    WO2021015122A1

  • Preparation method of nano metal film module and substrate preparation method

    CN110060973A

  • Method for producing a metal-ceramic substrate and furnace

    US20220411339A1